Methodology and preliminary results from the neurobiology of late-life depression study. (1st September 2015) - Steffens, David C.; Manning, Kevin J.; Wu, Rong; Grady, James J.; Fortinsky, Richard H.; Tennen, Howard A.
ABSTRACT: Background: We sought to investigate the relationship between neuroticism and depression in an elderly cohort. In this paper, we describe the methods of an National Institute of Mental Health—NIMH-supported study and present findings among the cohort enrolled to date. Methods: We used the NEO Personality Inventory to assess neuroticism, and we employed several cognitive neuroscience-based measures to examine emotional control. Results: Compared with a group of 27 non-depressed older control subjects, 33 older depressed subjects scored higher on measures of state and trait anxiety and neuroticism. On our experimental neuroscience-based measures, depressed subjects endorsed more negative words compared with controls on an emotional characterization test. In addition, we found a significant group-by-congruency effect on an emotional interference test where subjects were asked to identify the face's emotional expression while ignoring the words "fear" or "happy" labeled across the face. Conclusion: Thus, in this preliminary work, we found significant differences in measures of neuroticism and emotional controls among older adults with and without depression.